PENGARUH CEKAMAN KEKERINGAN TERHADAP PERTUMBUHAN BIBIT DAN ANATOMI AKAR Acacia auriculiformis Cunn., Tectona grandis L., Alstonia spectabilis Br., DAN Cedrela odorata L. - , ASRI CAHYANING P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Recent global warming has caused weather change and the increasing of temperature that lead to drought on earth. Environment that can absorb carbon emission, such as forest is essential. In order to preserve the forest, identification of drought adaptive species is needed. This research aims to determine physiological and anatomical responses of Acacia auriculifomis Cunn., Tectona grandis L., Alstonia spectabilis Br., and Cedrela odorata L. and the most adaptive species to drought. In this research, variations of drought treatment used were 10, 20, 30, and 40 days with control plants watered every 2 days. Each treatment had 3 replications. Physiological aspects observed were plant height, stem diameter, number and width of leaves, dry weight, proline content